TRANSLATIONAL POLICING: A PUBLIC POLICY APPROACH IN STRENGTHENING SOCIAL CONTROL OF JUVENILE DELINQUENCY IN URBAN AREAS - Haryanto Haryanto; Muhammad Mustofa (SOSIOEDUKASI, 2026)
Rapid social change in urban areas has weakened informal social control mechanisms and increased children's vulnerability to deviant behavior, making juvenile delinquency an ongoing public policy concern. This article aims to analyze translational policing as a public policy approach in strengthening social control over juvenile delinquency in urban areas. This study employs a qualitative approach through a literature review by examining scientific journal articles, academic books, and relevant policy documents, which are analyzed descriptively-analytically to identify concepts, patterns, and inter-variable relationships. The findings indicate that translational policing functions as a mechanism to bridge scientific evidence, policy formulation, and policing practice through the institutionalization of evidence use in policy governance. The findings also show that controlling juvenile delinquency is more effective when linked to the strengthening of social capital, collective efficacy, and family- and community-based protective factors, compared to purely repressive approaches. This study concludes that translational policing is relevantly positioned as a public policy approach that supports a more rational, preventive, and sustainable juvenile delinquency control strategy in urban areas.